2015
DOI: 10.3390/diseases4010001
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Carcinoma: Past and Future of Molecular Target Therapy

Abstract: Hepatocellular carcinoma (HCC) is one of the most common causes of cancer related mortality worldwide. The incidence of HCC has been increasing annually. Viral infection, alcohol usage, and other causes of cirrhosis have been identified as major risk factors for HCC development. The underlying pathogenesis has not been as well defined. There have been multiple hypotheses to the specific mechanisms of hepatocarcinogenesis and they share the common theme of chronic inflammation, increase oxidative stress, and ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 141 publications
(182 reference statements)
0
13
0
Order By: Relevance
“…Sorafenib targets cell surface tyrosine kinase receptors such as vascular endothelial growth factor receptor, platelet-derived growth factor receptor and epidermal growth factor receptor (EGFR) as well as serine/tyrosine kinases including Raf, FMS-like tyrosine kinase-3 (Flt-3) and c-kit. 55 An in vitro study demonstrated that sorafenib could efficiently reduce cell viability and induce apoptosis in HCC cell lines. 7 However, advanced HCC patients only had a survival benefit of 3 months after sorafenib monotherapy.…”
Section: The Role Of Cscs In the Livermentioning
confidence: 99%
“…Sorafenib targets cell surface tyrosine kinase receptors such as vascular endothelial growth factor receptor, platelet-derived growth factor receptor and epidermal growth factor receptor (EGFR) as well as serine/tyrosine kinases including Raf, FMS-like tyrosine kinase-3 (Flt-3) and c-kit. 55 An in vitro study demonstrated that sorafenib could efficiently reduce cell viability and induce apoptosis in HCC cell lines. 7 However, advanced HCC patients only had a survival benefit of 3 months after sorafenib monotherapy.…”
Section: The Role Of Cscs In the Livermentioning
confidence: 99%
“…Selected patients with localized disease may be treated with curative intents with resection, liver transplantation, or local therapy like radial frequency ablation, chemoembolization or radio-embolization. However, the majority of patients with HCC are not candidates for resection [104,105]. For patients suffering from advanced HCC, chemotherapy failed to demonstrate a survival advantage [106,107]; so far, sorafenib is the first and only target orientated agent approved as therapy of HCC [105], but it only extends survival of patients with advanced stage disease for 3 months, and this medication causes considerable adverse events and offers no symptom palliation [108].…”
Section: Getting Deeper Into Cirrhosis Resolution or Epigenetic Regulmentioning
confidence: 99%
“…Liver cancer is one of the most important factors in tumor-related death, threatening thousands of lives worldwide. 1,2 The most common pathological type in liver cancer is hepatocellular carcinoma (HCC) which arises from chronic liver inflammation and liver fibrosis mostly. 3,4 Nowadays, surgical resection and liver transplantation are the most widely used treatments for HCC internationally.…”
Section: Introductionmentioning
confidence: 99%